A single origin for the most frequent mutation causing late infantile metachromatic leucodystrophy. Issue 9 (September 1994) - Zlotogora, J; Furman-Shaharabani, Y; Harris, A; Barth, M L; von Figura, K; Gieselmann, V
Abstract : Metachromatic leucodystrophy is an autosomal recessive degenerative disease of the nervous system caused by the deficiency of the lysosomal enzyme arylsulphatase A (ARSA). We report here on the high incidence of late infantile MLD among Muslim Arabs originating from Jerusalem, most probably because of a founder effect. All the patients were found to be homozygous for 459 + 1 G-->A, a mutation which destroys the splice donor site of exon 2 of the ARSA gene. This mutation has been reported to be the most common mutation causing MLD. We studied the ARSA haplotype defined by three intragenic polymorphic sites in DNA samples from Muslim Arab patients from Jerusalem, a Christian Arab patient originating from the region, and eight other white patients, all homozygous for the 459 + 1 G-->A mutation. All the alleles carried the same haplotype which is in complete linkage disequilibrium with the mutation. This finding indicates a common origin for the 459 + 1 G-->A mutation which may have been introduced into Jerusalem at the time of the Crusades.